The Role of Parent Guidelines on the Achievement of Students in State 1st SMP - Christian Daniel Hermes (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to gain knowledge about the parental relationship with the learning outcomes of students in the field of study in the SMP N 1 Raya class VII based on data or facts right, true authentic, valid and reliable. This study uses a qualitative  approach, the data collected by using the interview method that will be tested with scientific method. The data collection technique that researchers use in this study is interview, 4 students will be chosen to be respondent. The respondent will give the question and they will be answer deeply and briefly, the answer will be collected and summoned to be an objective of this journal. Due to that, that answer also become the result of this research. Data processing using by using the qualitative method which had been arbitrated to the scientific research. The result is all respondent answer that the parental guiding is the most aspect that influence their result studies.